RESERVES FOR SHARIA LIFE INSURANCE CONTRIBUTIONS USING THE GROSS PREMIUM VALUATION (GPV) METHOD BASED ON VASICEK MODEL - Irawan, Wahri; Suwarman, Ramdhan Fazrianto; Azim, Muhamad Fadli; Sudrajat, Budi; Hamsyiah, Nurmaita (PATTIMURA UNIVERSITY, 2023)
Determining reserve for life insurance contributions has factors that influence it, such as contributions developed by participants and operational costs. Based on the financial services authority Number 71 of 2016, related to the company's financial health, one of which is that sharia insurance companies can make reserve for contributions. In this study, we discuss the calculation of the contribution of the initial value of return on investment which is sensitive and different calculations for the technical calculation of the contribution of sharia life insurance using the gross premium assessment method (GPV) by applying the Monte-Carlo simulation and using the vasicek model in calculating the discount factor so that with this method can recommend several possible contributions and contributions reserve from sharia life insurance products.